Role of Arabian female plastic artists in the art market: A comparative analysis study on selected samples of Arab countries - Alrasheed, Ibtesam S.; Sakr, Mohrah Hamed (Arte, Individuo y Sociedad, 2020)
When we try to recall the most famous artworks, what immediately comes to mind are works by male western artists, which makes us wonder about the role of women, especially Arabian women in the art world. This research utilizes the comparative analytical method to discuss the role of female Arabian artists in the Arab region and the western world’s art market. By first gathering data pertaining to works sold at auctions by female Arabian artists from the 20th and the 21st centuries, and who belong to both the eastern and western ends of the Arab world. Then analyzing and comparing the data to understand where women artists of the Arab world fit in the Arabian and Middle Eastern region art market. And to also understand the status of female versus male artist by comparing the highest prices reached by a work of art sold at an auction for artists of both sexes Arabian or western. Results show clear supremacy of male versus female artists in the art market whether in the Arab or the western worlds leading to the conclusion that women’s work is still valued significantly lower than that of men.